Urgensi Undang-Undang Penilai Dalam Memberikan Perlindungan dan Kepastian Hukum Bagi Penilai - Prasetyo, Arif Bagus; Abadi, Suwarno (Universitas Wijaya Putra, 2023)
The preamble of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) mandates the objectives of forming the Government of the Indonesian State. These objectives include the protection of the nation and all the blood of Indonesia, as well as the progress of public welfare, national education, and contributions to world order based on independence, eternal peace, and social justice. One of the efforts to achieve these objectives is by building the national economy as a collective endeavour based on the principle of togetherness. Article 33 of the 1945 Constitution regulates the national economy with economic democracy, the principles of togetherness, just and efficient justice, sustainability, and environmental awareness. The implementation of the fifth principle of Pancasila in economic development is stipulated in Article 33 paragraphs (1)-(5) of the 1945 Constitution. The Valuer profession plays a crucial role in supporting the national economy, providing economic value, and being an important institution in economic administration. However, the existence and role of Valuers also bring risks, such as legal claims against the opinions they produce. Clear norms and complaint mechanisms are needed to maintain the independence of Valuers. The current economic development process focuses on increasing productivity through diversification and technological innovation. The Valuer profession is rapidly growing in both the government and private sectors, including banking, capital markets, financial reporting, insurance, and land procurement. However, regulations related to the Valuer profession are scattered across several laws, which require clearer arrangements to ensure legal certainty and order. Therefore, legal protection in the form of regulations within the law is necessary to guarantee the important role and independence of the Valuer profession in supporting national economic development.